Experimental study of the anti-knock efficiency of high-octane fuels in spark ignited aircraft engine using response surface methodology. (1st February 2020) - Kumar, Thanikasalam; Mohsin, Rahmat; Majid, Zulkifli Abd.; Ghafir, Mohammad Fahmi Abdul; Wash, Ananth Manickam
Graphical abstract: Highlights: Anti-knock efficiency of 83 leaded/unleaded/blended fuels were investigated. Lycoming IO-540-K engine was used for optimisation using response surface method. Engine speed, fuel type and anti-knock efficiency responses were optimised. RSM AVGAS 100LL MS gave optimal solution of all 83 leaded/unleaded/blended fuels. 292.837 Hp, 777.557 Nm, 1099.521 kPa, 0.271 kg/kW h and 13.044 were the solutions. Abstract: Aviation gasoline contains tetraethyl lead to aid on knocking in spark-ignited aircraft engines. Tetraethyl lead in aviation gasoline is the cause of severe health effects and is considered as human carcinogenic compound. Piston aviation fuels initiative evaluated 245 unleaded fuels, but none could match all the performance regulations of aviation gasoline. In this study, optimisation of the knock-limited performance of 83 leaded/unleaded/blends was carried out. The input parameters were the fuels and engine speed. The output parameters were knock-limited data of brake horsepower, torque, brake mean effective pressure, brake specific fuel consumption and average air-to-fuel ratio. The engine speed was varied at 2350–2700 and the fuels were varied at eighty-three levels. The design matrix was selected based on one factor of response surface methodology which contained 581 experimental runs. Analysis of variance was performed on the models to validate the robustness of the model tested. Engine speed, type of fuel and average air-to-fuel ratio were set to be in range while brake horsepower, torque and brake mean effective pressure were maximised and brake specific fuel consumption was minimised. Confirmation test was carried out to validate the predicted and actual outcomes. Results indicated that when the engine was run with a speed of 2700 RPM, RSM AVGAS 100LL MS gave optimum solution with corresponding brake horsepower, torque, brake mean effective pressure, brake specific fuel consumption and average air-to-fuel ratio values of 292.837 Hp, 777.557 Nm, 1099.521 kPa, 0.271 kg/kW h and 13.044 respectively with a desirability of 0.972. The results indicated future focus of similar research into optimization of mid and low octane unleaded alternatives.